Political communication of generation Y via the Internet - Widera, Wiktor (Political Preferences, 2017)
The aim of this article is to present a fragment of the research results obtained during the implementation of the research project: "Communicating Policy Actors". The research was aimed at diagnosing the activity of the "Y" generation in political communication via the Internet. The research was conducted among the community of students studying in Katowice, at faculties of science, journalism, communication and new media. Apart from the assumed above-average use of new media tools by students, the rationale for directing research at students was their potential participation in professional life, in which they are consulted on everyday political activities. The research hypothesis was that the respondents were aware of the importance of their participation in political communication. Key words: political offer, politics, voters, relations, political activity, Internet